Understanding the process of sulphurisation from nano-mixed copper and silver nanoparticles - Teo, Alvin Yong Ler (Nanyang Technological University, 2023)
The reduction of carbon dioxide to create valuable multi-carbon products through electrochemistry is an appealing method for sustainable energy storage and reducing greenhouse gas emissions. Copper is the only known catalyst made of a single element that can produce various hydrocarbon and oxygenate products, including ethanol and ethylene. Recent studies have shown that nanostructured copper-silver alloys have even higher activity and selectivity towards multi-carbon production while suppressing hydrogen evolution. Therefore, precise control of the nanoscale alloying process between copper and silver is critical in optimizing copper/silver binary electrocatalysts. To achieve this, low-temperature annealing of copper and silver nanoparticles was performed to control the process. The study attempted to probe the diffusion behaviour of the catalysts at different temperatures. We found that copper and silver can form stable complete solid solutions at room temperature, as well as Janus particles that exhibit properties of both metals.